Composition-dependent transition in the magnetocrystalline anisotropy of tetragonal Heusler alloys Rh2TSb (T=Fe, Co) - Fecher, Gerhard H.; He, Yangkun; Felser, Claudia (Physical Review Materials, 2021)
This paper reports on first-principles calculations of the electronic and magnetic structure of tetragonal Heusler compounds with the composition Rh2FexCo1-xSb (0≤x≤1). It is found that the magnetic moments increase from 2 to 3.4 μB and the Curie temperature decreases from 500 to 464 K with increasing Fe content x. The 3d transition metals make the main contribution to the magnetic moments, whereas Rh contributes only approximately 0.2 μB per atom, independent of the composition. The paper focuses on the magnetocrystalline anisotropy of the borderline compounds Rh2FeSb, Rh2Fe0.5Co0.5Sb, and Rh2CoSb. A transition from easy-axis to easy-plane anisotropy is observed when the composition changes from Rh2CoSb to Rh2FeSb. The transition occurs at an iron concentration of approximately 40%. The difference in the anisotropy is caused by differences in the charge and spin distributions, mainly at Fe and Co. The results of the calculations are in good agreement with recent experiments.
CRIS-Team Scopus Importer:2022-04-14